Neomodified Koyanagi technique for severe hypospadias with one‐stage sealed Y‐shaped penis foreskin vascular protection surgery. Issue 3 (17th March 2022) - Zu, Jiancheng; Chen, Yifu; Liu, Yu; He, Tianqu; Wang, Yanling; Zu, Yuee; Peng, Xiangwen
Abstract: Proximal hypospadias defects represent the most challenging aspect of maintaining blood supply to the flap, which eventually leads to a high rate of complications. We modified a sealed Y‐shaped penis foreskin vascular protection technique, which can repair the urethra in a single stage. The inner plate of the foreskin was cut along the coronal sulcus, and both sides of the urethral plate were cut as deep as Buck's fascia. The "Y"‐shaped foreskin flaps on both sides of the mouth that are continuous with the urethral plate were sutured to form a new urethral skin tube. The urethral skin tube was turned to the ventral side, and the foreskin was reshaped and sutured. A total of 89 children had their urinary catheters removed 4 weeks after the operation. All children were evaluated at least once a year for 3 consecutive years. There were 11 patients with urine leakage that occurred after the operation. These children, diagnosed with urine leakage, underwent successful repair after the leakage occurred. There were no urethral strictures after the operation. The one‐time success rate of this operation was 87.6% (78/89), and the incidence of urethral fistula was 12.6% (11/89). The results showed that sealed Y‐shaped penis foreskin vascular protection surgery was safer and had a higher operation rate than the traditional hypospadias repair technique. Modifying Koyanagi repair by our improved Koyanagi hypospadias repair is an excellent technique with relatively low complication rates. Abstract : We designed a closed Y‐shaped flap repair. In this operation, we used the Y‐shaped flap to synthesize a new urethra. The unique incision to protect the vascular system of the Y‐shaped flap enables one‐time repair of hypospadias with complete repair of penile curvature with low complication rate.